Evaluating Barriers to SNAP/EBT Acceptance in Farmers Markets: A Survey of Farmers - Krysta Kellegrew; Alicia Powers; Barb Struempler; Sondra Parmer; Katie Funderburk; Jamie Griffin; Cecilia Tran (Journal of Agriculture, Food Systems, and Community Development, 2018)
Farmers play a critical role in increasing access to and affordability of fruits and vegetables in low-income communities by accepting Supplemental Nutrition Assistance Program (SNAP) benefits at farmers markets. However, only 40% of farmers markets nationally accept SNAP benefits. This study evaluates barriers farmers perceive in accepting SNAP in farmers markets. We recruited 134 farmers using convenience sampling from six pre-season regional growers meetings hosted in Alabama; 92 farmers met inclusion criteria and completed the anonymous, 51-question survey. The survey measured demographics, perceived barriers and promotional opportunities within constructs of the Social Ecological Model (SEM). We used descriptive statistics to summarize characteristics, and chi-square, Mann-Whitney U and t-tests to analyze differences in characteristics between those farmers who accept SNAP and those who do not. The most frequently cited barriers to SNAP acceptance included lack of internet access, increased burden for processing payments, increased need for bookkeeping, limited availability of information about the application process and payment system, limited support from the market for completing the application, a small customer base and limited number of SNAP clientele. Comparative analyses revealed statistically significant differences in demographics and perceived barriers between those who accept SNAP and those who do not. Findings from this study provide a more in-depth understanding of challenges farmers face in accepting SNAP. These can be addressed through education, policy, systems and environmental solutions at various levels of the SEM to overcome barriers to SNAP acceptance, ultimately increasing access to and affordability of fruits and vegetables for low-income communities.